A study on the interface between an amorphous chalcogenide and the electrode: Effect of the electrode on the characteristics of the Ovonic Threshold Switch (OTS) - Seo, Juhee; Cho, Seong Won; Ahn, Hyung-Woo; Cheong, Byung-Ki; Lee, Suyoun (ELSEVIER SCIENCE SA, 2017)
We have studied the effect of the electrode material on the switching behavior of the Ovonic Threshold Switch (OTS) composed of metal/amorphous Ge60Se40/metal. The switching voltage is found to depend strongly on the electrode material, showing a much lower value (similar to 1.74 V) for Mo compared to that (similar to 5.85 V) of TiN. As the origin, the Schottky barrier and the interface trap states are examined, leading to a conclusion that the latter plays a crucial role. These results are interpreted by a picture of carrier transport at a metal/amorphous chalcogenide interface, providing an effective method to modulate the switching characteristics of the OTS device for various applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: SEMICONDUCTORS; STATES; MODEL; ALLOYS; GLASS; GAP